Knowledge and attitude of married Turkish men regarding family planning - Pirincci, E.; Oguzoncul, A. F. (Informa Healthcare, 2008)
Objectives Men play an essential role in reproduction. They should be encouraged to involve themselves in birth control, particularly in developing countries, where contraceptive goals have not been reached. This study, carried out in Mu, Turkey, was aimed at determining the attitudes and behaviour of married men with regard to family planning (FP). Methods The study included 317 married men aged 20-56 who worked in an institution. Questionnaires were distributed to the participants at their workplace and collected after 3040 minutes. Results The use of FP was approved by 78.9% of the men, but a contraceptive method was actually applied by only 65.6%. Whereas 27.6% of the high school and university graduates had five or more children, as many as 67.4% of the men with a lesser educational level had such a large offspring. Nearly 60% of the men had been given information about FP by healthcare professionals. Conclusion Education has a great impact on knowledge and attitudes about FP.
Keywords: attitudes; contraception; family planning; knowledge; married men